Effects of weight loss on myocardial energetics and diastolic function in obesity. - Rider, O; Francis, J; Tyler, D; Byrne, J; Clarke, K; Neubauer, S (2013)
A reduced myocardial phosphocreatine/adenosine triphosphate (PCr/ATP) ratio is linked to both diastolic dysfunction and heart failure. Although obesity is well known to cause diastolic dysfunction a link to impaired cardiac energetics has only recently been established. We assessed whether or not long-term weight loss in obesity, which is known to reduce mortality, is accompanied by both improved cardiac energetics and diastolic function. Normal weight (BMI 22 ± 2; n = 18) and obese subjects (BMI 34 ± 4; n = 13) underwent cine-MRI (1.5 Tesla) to determine left ventricular diastolic function using volume-time curve analysis, and (31)P-MR spectroscopy (3 Tesla) to assess cardiac energetics (PCr/ATP ratio). Obese subjects (n = 13) underwent repeat assessment after 1 year of supervised weight loss. Obesity, in the absence of identifiable cardiovascular risk factors, was associated with significantly impaired myocardial high energy phosphate metabolism (PCr/ATP ratio, normal; 2.03 ± 0.27 vs. obese; 1.58 ± 0.47, p = 0.002) and significantly lower peak diastolic filling rate (normal; 4.8 ± 0.8 vs. obese; 3.8 ± 0.7 EDV/s, p = 0.01). Weight loss (on average 9 kg, 55% excess weight) over 1 year resulted in a 24% increase in PCr/ATP ratio (p = 0.01) and an 18% improvement in peak diastolic filling rate (p = 0.01). Myocardial PCr/ATP ratio remained positively correlated with peak diastolic filling rate after weight loss (r = 0.63, p = 0.02). In obesity, weight loss improves impaired cardiac energetics and myocardial relaxation. Improved myocardial energetics appear to play a key role in diastolic functional recovery accompanying weight loss.